The Effect of Semantic Similarity on Learning Ambiguous Words in a Second Language: An Event-Related Potential Study - Zhang, Yuanyue; Lu, Yao; Liang, Lijuan; Chen, Baoguo (Frontiers in Psychology, 2020)
Ambiguous words have multiple meanings. How these multiple meanings interact with each other during ambiguous word learning remains unclear. The current study adopted an event-related potentials (ERPs) technique to explore whether there is an interaction between two meanings when learning second language (L2) ambiguous words and how semantic similarity affects ambiguous word learning. In order to explore this issue, Chinese-English bilinguals were asked to learn pseudowords, which were paired with either two related new meanings (polysemes), two unrelated new meanings (homonyms), or one single new meaning (monosomies) over 2 consecutive days. ERP results revealed that learning the second meaning of a homonym induced a more negative N400 than the first meaning; learning the second meaning of a polyseme tended to produce a more positive late component (LPC) than the first meaning. These results indicate that the first meaning of homonyms may interfere with learning their second meaning. However, the first meaning of polysemous words may facilitate learning their second meaning. The current findings suggest that different mechanisms might be involved in learning L2 homonyms and polysemes.